P144 Adherence to inhaled corticosteroids in pregnant asthmatics. (11th November 2022) - Sandar, AE; Bradley, ER; Baron, R; Paterson, SL; Khan, WA
Abstract : Introduction: Adherence to asthma medications is generally low and may be detrimental to clinical outcomes (Robijn et al, 2019). 1 Poor adherence is characterized by underuse of inhaled corticosteroids (ICS), often accompanied by over-reliance on short-acting β2 -agonists for symptom relief. Poor adherence to ICS is of particular concern in pregnant asthmatics and may be the result of historical poor compliance or medication cessation during pregnancy, incorrectly or by choice. Objectives: We studied pregnant asthmatics referred to our obstetric asthma service in order to assess compliance with ICS treatment. Methods: A retrospective analysis was performed for 50 patients referred to obstetric asthma clinic between July 2018 and February 2021 at Manchester Royal Infirmary. Data were collated from General Practice (GP) medication records for ICS pick-up rates (%) for the six months before pregnancy, during the first trimester and two months following their first clinic review. Good compliance was defined as ≥70%. Results: Only two patients (4%) achieved the ≥70% pick-up rate for ICS treatment in the six-month period prior to pregnancy and this decreased to 2% during the first trimester. However, the rate of compliance increased to 30% (n=15) following their first obstetric asthma clinic review. 42% reported concerns regarding medication risk to pregnancy as being a significant factor in non-compliance (n=21). Conclusion: Poor compliance to ICS treatment in asthma is not confined to pregnant asthmatics and may be a historical finding in these patients. However, an increase in ICS adherence following clinic review indicates that education and reinforcement of medication safety and importance of adherence to treatment is essential in this cohort and will undoubtedly improve clinical outcomes and reduce the risk of exacerbations. Patient concerns relating safety of inhaled therapies in pregnancy should be addressed early to improve patient outcomes in the high risk group. Trends to poor compliance in the absence of clinic review has led to the evolution of monthly appointments until review until delivery, rather than early discharge. Reference: Robijn, A L., Jensen, M E., McLaughlin, K., Gibson, P G., Murphy, V E. (2019). Inhaled corticosteroid use during pregnancy among women with asthma: A systematic review and meta-analysis. Clinical & Experimental Allergy. https://doi.org/10.1111/cea.13474